The fludarabine, cytarabine, and granulocyte colony‐stimulating factor (FLAG) chemotherapy regimen is an alternative to anthracycline‐based therapy for the treatment of acute myeloid leukemia for patients with pre‐existing cardiac disease. (3rd May 2016) - Saini, Lalit; Brandwein, Joseph; Turner, Robert; Larratt, Loree; Hamilton, Marlene; Peters, Anthea; Wu, Cynthia; Zhu, Nancy; Patterson, Jeffery M.; Bolster, Lauren; Mant, Michael; Ritchie, Bruce; et al.
Abstract: We conducted a retrospective study assessing FLAG (fludarabine, cytarabine, and granulocyte colony‐stimulating factor) as first‐line treatment in 56 newly diagnosed acute myeloid leukemia patients considered ineligible for anthracycline‐based treatment due to advanced age, significant comorbidities, or pre‐existing cardiac disease. The median age was 69 (21–80); 46% received FLAG for pre‐existing cardiac disease and others due to age (32%), non‐cardiac comorbidities (20%), or previous anthracycline exposure (2%). The induction mortality was 16% and, among evaluable patients, 48% achieved a complete remission after the first induction course with an additional patient achieving a remission after a second course for a total complete remission rate of 50%. Four patients proceeded to an allogeneic stem cell transplant including two with pre‐existing cardiac disease. Among non‐transplanted patients, the relapse rate (RR) was 47%. When censored at time of stem cell transplant, the median relapse‐free survival was 14.7 months. The median overall survival was 9.3 months with 1‐ and 2‐yr survivals of 44% and 22%, respectively. There was no difference in clinical outcomes between patients treated with FLAG for cardiac reasons vs. other reasons. In conclusion, FLAG is a useful alternative to anthracycline‐based induction for Acute myeloid leukemia in those with significant comorbidities including pre‐existing cardiac disease.